Whole Transcription Profile of Responders to Anti-TNF Drugs in Pediatric Inflammatory Bowel Disease - Sara Salvador-Martín; Bartosz Kaczmarczyk; Rebeca Álvarez; Víctor Manuel Navas-López; Carmen Gallego-Fernández; Ana Moreno-Álvarez; Alfonso Solar-Boga; Cesar Sánchez; Mar Tolin; Marta Velasco; Rosana Muñoz-Codoceo; Alejandro Rodriguez-Martinez; et al. (MDPI AG, 2021)
Background: Up to 30% of patients with pediatric inflammatory bowel disease (IBD) do not respond to anti-Tumor Necrosis Factor (anti-TNF) therapy. The aim of this study was to identify pharmacogenomic markers that predict early response to anti-TNF drugs in pediatric patients with IBD. Methods: An observational, longitudinal, prospective cohort study was conducted. The study population comprised 38 patients with IBD aged < 18 years who started treatment with infliximab or adalimumab (29 responders and nine non-responders). Whole gene expression profiles from total RNA isolated from whole blood samples of six responders and six non-responders taken before administration of the biologic and after two weeks of therapy were analyzed using next-generation RNA sequencing. The expression of six selected genes was measured for purposes of validation in all of the 38 patients recruited using qPCR. Results: Genes were differentially expressed in non-responders and responders (32 before initiation of treatment and 44 after two weeks, Log2FC (Fold change) >0.6 or <−0.6 and p value < 0.05). After validation, FCGR1A, FCGR1B, and GBP1 were overexpressed in non-responders two weeks after initiation of anti-TNF treatment (Log2FC 1.05, 1.21, and 1.08, respectively, p value < 0.05). Conclusion: Expression of the FCGR1A, FCGR1B, and GBP1 genes is a pharmacogenomic biomarker of early response to anti-TNF agents in pediatric IBD.